2005
DOI: 10.3390/10020475
|View full text |Cite
|
Sign up to set email alerts
|

5-Furan-2yl[1,3,4]oxadiazole-2-thiol, 5-Furan-2yl-4H [1,2,4] triazole-3-thiol and Their Thiol-Thione Tautomerism

Abstract: 5-Furan-2-yl[1,3,4]oxadiazole-2-thiol (Ia) and 5-furan-2-yl-4H-[1,2,4]- triazole-3-thiol (Ib) were synthesized from furan-2-carboxylic acid hydrazide. Mannich bases and methyl derivatives were then prepared. The structures of the synthesized compounds were confirmed by elemental analyses, IR and 1H-NMR spectra. Their thiol-thione tautomeric equilibrium is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…[19][20][21][22] S-Alkylation of compound 1 with either substituted phenacyl bromides, bromochloroethane or ethyl chloroacetate * To whom correspondence should be addressed. e-mail: Aliaa.kamal@pharma.cu.edu.eg; k_aliaa2511@hotmail.com The infrared (IR) spectra of both compounds 4 and 5 showed disappearance of absorption bands corresponding to C=O function.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22] S-Alkylation of compound 1 with either substituted phenacyl bromides, bromochloroethane or ethyl chloroacetate * To whom correspondence should be addressed. e-mail: Aliaa.kamal@pharma.cu.edu.eg; k_aliaa2511@hotmail.com The infrared (IR) spectra of both compounds 4 and 5 showed disappearance of absorption bands corresponding to C=O function.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 4-allyl-5-pyridin-4-yl-4H-1,2,4-triazole-3-thiol was carried out according to a method are given in the literature 24 . The structures of synthesized compounds were confirmed by analytical and spectroscopic methods (FT-IR, 1 H NMR, 13 C NMR).…”
Section: Methodsmentioning
confidence: 99%
“…Koparir et al reported that the crystal structure of thiol compounds corresponded to the thione form, but they showed thiol-thione tautomerism in solutions (Figure 2) 24 . Due to the thiol-thione tautomerism of 4-allyl-5-pyridin-4-yl-4H-1,2,4-triazole-3-thiol it mostly appeared thiol form in solution.…”
Section: Electrochemical Behavior Of 4-allyl-5-pyridin-4-yl-4h-124-mentioning
confidence: 99%
“…Starting from pyroglutamic esters, 1,2,4-triazole-3-thiones 12 44 , bonded to a pyrrolidinone 5-Furan-2-yl-4H-1,2,4-triazole-3-thiol (14) was prepared by the reaction of the appropriate 2-furoyl-thiosemicarbazide (13) and potassium hydroxide in ethanol for 3 hours under reflux, followed by acidification with acetic acid 45,46 (Scheme 6). It has been reported that the crystal structure of 3 corresponded to the thione form, but they showed thiol-thione tautomerism in solution 47 .…”
Section: Methodsmentioning
confidence: 99%